2016
DOI: 10.1002/bip.22874
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acidic pH on the stability of α‐synuclein dimers

Abstract: Environmental factors, such as acidic pH, facilitate the assembly of α-synuclein (α-Syn) in aggregates, but the impact of pH on the very first step of α-Syn aggregation remains elusive. Recently, we developed a single-molecule approach enabling us to measure directly the stability of α-Syn dimers. Unlabeled α-Syn monomers were immobilized on a substrate, and fluorophore-labeled monomers were added to the solution to allow them to form dimers with immobilized α-Syn monomers. The dimer lifetimes were measured di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 30 publications
1
26
0
Order By: Relevance
“…It was suggested that these observations could be explained by the possibility that the dimerization propensity of the asyn proteins to form dimers does not reflect their oligomerization and aggregation properties (Eckermann et al, 2015). However, this interpretation is not consistent with extensive biophysical studies using alternative approaches that show significant differences in the propensity of a-syn with the various PD-linked a-syn mutants to form oligomers (Winner et al, 2011) and dimers (Janowskaet al, 2015;Lv et al, 2016). In addition, several studies have shown significant differences in the lifetime and distribution of different types of dimers formed by wild-type a-syn and PD-linked mutants (Krasnoslobodtsev et al, 2013;Krishnan et al, 2003;Lv et al, 2015).…”
Section: Discussionmentioning
confidence: 98%
“…It was suggested that these observations could be explained by the possibility that the dimerization propensity of the asyn proteins to form dimers does not reflect their oligomerization and aggregation properties (Eckermann et al, 2015). However, this interpretation is not consistent with extensive biophysical studies using alternative approaches that show significant differences in the propensity of a-syn with the various PD-linked a-syn mutants to form oligomers (Winner et al, 2011) and dimers (Janowskaet al, 2015;Lv et al, 2016). In addition, several studies have shown significant differences in the lifetime and distribution of different types of dimers formed by wild-type a-syn and PD-linked mutants (Krasnoslobodtsev et al, 2013;Krishnan et al, 2003;Lv et al, 2015).…”
Section: Discussionmentioning
confidence: 98%
“…Recent studies have demonstrated that single-molecule approaches are powerful methods to study oligomers. [43][44][45][46] Single-molecule techniques, such as AFM, 11,[47][48][49][50][51] tethered approach for probing inter-molecular interactions (TAPIN), 52,53 and FRET, 33 have shown that the early-stage oligomers exhibit prolonged lifetimes and stabilities. Novel features of the interaction and self-assembly of Ab40 and Ab42 peptides were determined using single-molecule AFM-based force spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…39 More recently, the design of peptides that specifically bind to strands F and H of TTR have been shown to effectively work as amyloid inhibitors by capping those strands and preventing head-to-head association of TTR monomers. 17 The particular relevance of dimers over other similar low molecular weight aggregates (eg, trimers, tetramers, and pentamers) is not exclusive to TTR and has been reported in a variety of amyloidogenic systems such as peptides Aβ 40 and Sup35, 41 as well as proteins, including αsynuclein 42,43 and β2-microglobulin. 44 Thus, it is conceivable that the arrangement of monomers along the aoTTR annuli might result in alternating strongly and weekly interacting monomer-monomer interfaces, with the strong interfaces associated with dimer formation and weak interfaces defining the dimer outer limits.…”
Section: Contour Length Of Manipulated Chainsmentioning
confidence: 99%